PERISAI COMPETENCE IN INCREASING SOCIAL SECURITY ADMINISTRATOR FOR EMPLOYMENT MEMBERSHIP IN MEDAN - Irawan, Muhammad Ari; Wibowo, Rulianda Purnomo; Sadalia, Isfenti (UTSAHA: Journal of Entrepreneurship, 2023)
The government's efforts in providing social protection to workers is by creating department that can provide social protection to every worker in Indonesia known as Social Security Agency (BPJS) which is a public legal entity that manages 4 of the 5 social security programs in Indonesia. This research aims to analyze perisai competency strategies in increasing membership of BPJS Ketenagakerjaan in Medan. This research is located at BPJS Ketenagakerjaan Medan City Branch using thirty-nine Perisai agents. This research used six respondents through questionnaires using five Likert scales and nine Likert scales. The Delphi Panel method uses thirteen competencies with three competency categories, called intellectual competence, emotional competence and social competence. This research uses Analytic Hierarchy Process (AHP) method which aims to analyze priority competencies. Based on the research result using Delphi Panel method, it found thirteen competencies grouped into three categories including intellectual competence, emotional competence and social competence indicating that there were no priorities in covering intellectual competence, emotional competence and social competence.